Geochemical Approach to Determine the Possible Precipitation Parameters of the Coniacian-Santonian Mazidagi Phosphates, Mardin, Turkey - Gundogar, Derya Yildirim; Sasmaz, Ahmet (Mdpi, 2022)
The Tethyan phosphates were formed during the Upper Cretaceous and Eocene interval as a result of the collision of the African-Arabian and Eurasian plates and the closing of the Neo-Tethys Ocean. This study aimed to reveal the possible precipitation parameters of these phosphates by examining the main oxide, trace element, and rare earth element contents of the phosphates in the study region. The mean major oxide concentrations of the phosphates were found to be 51.6 wt.% CaO, 21.2 wt.% P2O5, 8.03 wt.% SiO2, 18.1 wt.% CO2, 0.51 wt.% K2O, 0.12 wt.% Fe2O3, 0.05 wt.% Al2O3, 0.18 wt.% MgO, and 0.02 wt.% MnO. The average trace element concentrations were 79 ppm Ba, 1087 ppm Sr, 0.23 ppm Rb, 14.7 ppm Ni, 108 ppm Cr, 262 ppm Zn, 27 ppm Cd, 21.6 ppm Y, 58 ppm V, 6.43 ppm As, 30.3 ppm Cu, 1.36 ppm Pb, 6.32 ppm Zr, 39 ppm U, 0.21 ppm Th, and 1.33 ppm Co. The average trace element contents were 1742 ppm, with this indicating an enrichment assemblage of Sr, Cd, As, and Zn in comparison to PAAS (The Post-Archean Australian Shale). The total REE concentrations in the Mazidagi phosphates varied from 3.30 to 43.1 ppm, with a mean of 22.1 ppm recorded. All phosphates showed heavy REE (HREE) enrichments and had similar REE patterns to PAAS (The Post-Archean Australian Shale). All samples had strongly negative Ce and positive Eu, Pr, and Y anomalies. These anomalies indicate the existence of oxic and suboxic marine conditions during the formation of the phosphates. According to the proposed genetic model, the phosphates mostly formed in the oxic and suboxic zones of the Tethys Ocean and were precipitated on slopes that depended on strong upwelling from an organic-rich basin in anoxic/suboxic conditions from deeper seawater. The Pb isotope data obtained also indicate the existence of a deep-sea hydrothermal contribution to this phosphate formation.
Keywords: phosphate; Coniacian-Santonian; REE geochemistry; Mazidagi; Turkey